Taekwondo: Bagaimanakah Kondisi Fisik Atlet Di Dojang Speed Kick Kota Pekanbaru - Yunus Perimsa Sembiring; Oki Candra (Journal on Education, 2024)
The aim of this research was to see the level of physical condition of taekwondo athletes at the speed kick dojang in Pekanbaru City. Based on the results of observations of taekwondo athletes at the speed kick dojang in Pekanbaru City, several problems were found, including the unknown physical condition of the taekwondo athletes at the speed kick dojang in the taekwondo sport, in training that was held three times a week, the physical training portion was not enough to improve physical condition and In the competition, the quality of the athlete's physical condition when they are on the field is seen to decrease greatly, causing the quality of the athlete's competition to be less than satisfactory. The tests used in this research using taekwondo physical condition tests include fitness muscle strength (leg dynamometer), speed test (30 meter sprint), leg dynamometer test, squat jump test, vertical jump test, 50 meter sprint test, sitting test and reach and test run 15 minutes. The sample in this study was 17 taekwondo athletes at the speed kick dojang in Pekanbaru City. From the results of tests carried out in the field, results were obtained in the "Fair" category and were proven by an average value of 6.22 or in the interval 6.0 – 7.9.